Metabolic reprogramming in chondrocytes to promote mitochondrial respiration reduces downstream features of osteoarthritis - Ohashi, Yoshifumi (Sci Rep, 2021)
Metabolic dysfunction in chondrocytes drives the pro-catabolic phenotype associated with osteoarthritic cartilage. In this study, substitution of galactose for glucose in culture media was used to promote a renewed dependence on mitochondrial respiration and oxidative phosphorylation. Galactose replacement alone blocked enhanced usage of the glycolysis pathway by IL1β-activated chondrocytes as detected by real-time changes in the rates of proton acidification of the medium and changes in oxygen consumption. The change in mitochondrial activity due to galactose was visualized as a rescue of mitochondrial membrane potential but not an alteration in the number of mitochondria. Galactose-replacement reversed other markers of dysfunctional mitochondrial metabolism, including blocking the production of reactive oxygen species, nitric oxide, and the synthesis of inducible nitric oxide synthase. Of more clinical relevance, galactose-substitution blocked downstream functional features associated with osteoarthritis, including enhanced levels of MMP13 mRNA, MMP13 protein, and the degradative loss of proteoglycan from intact cartilage explants. Blocking baseline and IL1β-enhanced MMP13 by galactose-replacement in human osteoarthritic chondrocyte cultures inversely paralleled increases in markers associated with mitochondrial recovery, phospho-AMPK, and PGC1α. Comparisons were made between galactose replacement and the glycolysis inhibitor 2-deoxyglucose. Targeting intermediary metabolism may provide a novel approach to osteoarthritis care.